1989
DOI: 10.1149/1.2096511
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion of Carbon Black Anodes in Alkaline Electrolyte: IV . Current Efficiencies for Oxygen Evolution from Metal Oxide‐Impregnated Graphitized Furnace Blacks

Abstract: A quantitative method for determining the number of oxygenated carbon atoms in a carbon black sample was developed and applied to the study of oxygen chemisorption on graphitized furnace blacks. It was found that chemisorption of oxygen atoms produced in a low‐pressure microwave discharge of argon/oxygen results in the formation of an oxygen complex on every carbon atom exposed on the edge plane surface of these carbons. These combined procedures were then used to titrate the surfaces of a variety of graphitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…The findings presented in the previous section reveal that Pt (and Pd) nanoparticles are not subjected to severe dissolution (and possible redeposition) and that their carbon support is not suffering extensive corrosion. However, Ross et al have measured (both solid and liquid) carbonates formation from carbon black degradation in alkaline environments, and in more severe conditions (higher temperatures and potentials than those considered in the present study) gaseous CO 2 evolution . In order to track such carbonate species, FTIR spectroscopy is a tool of choice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings presented in the previous section reveal that Pt (and Pd) nanoparticles are not subjected to severe dissolution (and possible redeposition) and that their carbon support is not suffering extensive corrosion. However, Ross et al have measured (both solid and liquid) carbonates formation from carbon black degradation in alkaline environments, and in more severe conditions (higher temperatures and potentials than those considered in the present study) gaseous CO 2 evolution . In order to track such carbonate species, FTIR spectroscopy is a tool of choice.…”
Section: Resultsmentioning
confidence: 99%
“…Both processes counterbalance the passivation by solid carbonates, which is very detrimental to the carbon support durability . Graphitized carbon (more organized, with less edge atoms) was proven more robust against corrosion , , but the presence of electrocatalyst nanoparticles (usually 3d transition metals or oxides: Ni, Fe, Cr) dramatically enhances the corrosion rate of carbon . Although PGM nanoparticles have not been investigated in these earlier studies, one can postulate that, as demonstrated for acidic corrosion of PEMFC electrocatalysts , , the presence of metal (e.g., Pt) nanoparticles at the carbon surface and the alternation of high/low potential values (or of oxidizing/reducing conditions) further increases the destabilization of the carbon surface and could also destabilize the metal nanoparticles, which are immobilized at its surface .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the accumulation of oxygen always causes the formation of humic acid in the solution . Studies show that increasing the graphite content of the carbon causes its resistance to oxidation to carbon dioxide . In alkaline solutions (pH between 11 and 13) at high current densities, carbon dioxide accumulation prevails and at low current densities oxygen enrichment prevails …”
Section: Introductionmentioning
confidence: 99%
“…[13] Studies show that increasing the graphite content of the carbon causes its resistance to oxidation to carbon dioxide. [14] In alkaline solutions (pH between 11 and 13) at high current densities, carbon dioxide accumulation prevails and at low current densities oxygen enrichment prevails. [11] Pruckner [15] applied conductive coating as strips over and between the primary anode wires, which were fixed in concrete before.…”
Section: Introductionmentioning
confidence: 99%